Is the Recurrence of Fibroma of the Tendon Sheath Underestimated? An Instructive Case Report and a Review of the Literature - E. Lüdke; G. Kohut; H. C. Bäcker; M. Maniglio (Case Reports in Orthopedics)
We report a case of a 21-year-old healthy woman with a history of a painful growing mass in the palm of the right hand, with a trigger finger phenomenon. The mass was surgically entirely excised, and the histological findings of the tumor were those of a fibroma of the tendon sheath (FTS) starting from the flexor tendons. Although the initial outcome was good, the patient experienced the same symptoms at the same location 4.5 years later. The MRI demonstrated a 50×10×5 mm mass of low intensity on T1-weighted images and high intensity on T2-weighted images and gadolinium enhancement. A second complete excision of the tumor was performed by the same senior surgeon, and the histology confirmed the recurrence of the FTS. We also reviewed the scientific literature about FTS in the hand. Most recent studies show a low rate or no recurrence at all. We hypothesize that a lot of recurrences are missed because of a short follow-up and that the recurrence rate may be higher than thought.